The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1038/s41419-023-05866-1
|View full text |Cite
|
Sign up to set email alerts
|

METTL3-dependent m6A methylation facilitates uterine receptivity and female fertility via balancing estrogen and progesterone signaling

Abstract: Infertility is a worldwide reproductive health problem and there are still many unknown etiologies of infertility. In recent years, increasing evidence emerged and confirmed that epigenetic regulation played a leading role in reproduction. However, the function of m6A modification in infertility remains unknown. Here we report that METTL3-dependent m6A methylation plays an essential role in female fertility via balancing the estrogen and progesterone signaling. Analysis of GEO datasets reveal a significant dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…19 The significance of m 6 A modification in embryo implantation remains unclear. In recent studies, Zheng et al 20 and Wan et al 21 revealed the m 6 A-mediated mechanisms for ensuring normal progesterone and estrogen signaling during embryo implantation. Uterine-specific deletion of the m 6 A writer METTL3 culminates in implantation failure due to preimplantation embryo loss and compromised uterine receptivity.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…19 The significance of m 6 A modification in embryo implantation remains unclear. In recent studies, Zheng et al 20 and Wan et al 21 revealed the m 6 A-mediated mechanisms for ensuring normal progesterone and estrogen signaling during embryo implantation. Uterine-specific deletion of the m 6 A writer METTL3 culminates in implantation failure due to preimplantation embryo loss and compromised uterine receptivity.…”
Section: Reviewmentioning
confidence: 99%
“…Specifically, m 6 A-seq analysis identified m 6 A modifications in the 3′ untranslated region of several estrogen-responsive genes, mRNAs of which exhibited increased stability upon METTL3 depletion. 21 In addition to posttranscriptional regulation, steroid nuclear receptor activities are also regulated by posttranslational modifications, such as phosphorylation and ubiquitination. 22,23 Tang et al 24 recently reported that uterine deficiency of p38α-impaired uterine receptivity ascribed to reduced PR protein levels and reduced progesterone responsiveness in the uterine stroma.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…METTL3 directly regulates the expression levels of classical oncogenes or tumor suppressor genes, reflecting its important role in tumor progression. It also exerts methyltransferase activity, guiding the transcription of MYC mRNA and promoting the progression of PCa (Wan et al, 2023). Furthermore, the cancer-promoting factor METTL3 and its upstream cofactor YTH domain family 2 protein (YTHDF2), were identified as the key "writer" and "reader" of m6A modification, facilitating mRNA degradation of tumor suppressor lipid phosphatase and NK3 homeobox 1 and promoting the proliferation and migration of PCa cells.…”
Section: Pseudouridine (ψ)mentioning
confidence: 99%